2011
DOI: 10.1111/j.2042-3306.2010.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of joint injuries in Thoroughbred racehorses in training

Abstract: Carpal and MCP/MTP joint injuries are an important cause of morbidity in Thoroughbred racehorses. Identification of modifiable risk factors for these injuries may reduce their incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 26 publications
5
45
0
6
Order By: Relevance
“…There was a lower prevalence of lucencies in the Cu bone in the current study. It has been found that ulnar carpal bone lucencies and associated fragments can be an incidental finding in horses from all disciplines 23 . It is difficult to explain this lower prevalence in the South African Thoroughbred yearling population.…”
Section: Discussionmentioning
confidence: 99%
“…There was a lower prevalence of lucencies in the Cu bone in the current study. It has been found that ulnar carpal bone lucencies and associated fragments can be an incidental finding in horses from all disciplines 23 . It is difficult to explain this lower prevalence in the South African Thoroughbred yearling population.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal injuries (MSI) are the primary cause of reduced training days and racehorse wastage in Standardbred racehorses (STBR) as well as in Thoroughbred racehorses (TBR) [1-6]. But, only a few research studies have attentively focused on STBR specific problems [7-10], such as middle carpal joint injuries [8] and proximal sesamoid bone fractures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Racetrack surface [2,3], age [1,3,6], gender [1,6,16,17], season [3,5,16], trainer [4,5,15-17], pre-existing pathologies [18-20], accumulation of exercise at racing speed [21,22], average distance run per week [23,24], laying-up periods [2,22] and inter-race interval [2,22] have all been studied in TBR populations, with contradictory results. Also, shoeing techniques received great attention [19,25,26]; particularly one of them, the toe grab, is a recognized risk factor for MSI in TBR due to the alteration of the horse’s gait at high speed [19,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence and risk factors for musculoskeletal injuries are best documented in the racing Thoroughbred (Stover et al 1992 ;Parkin et al 2006 ;Verheyen et al 2006 ;Clegg 2011 ;Reed et al 2012 ). The reason is the structured nature of the race industry with information on the individual animal (age at fi rst race, number of starts, winning sum) readily available.…”
Section: Resultsmentioning
confidence: 99%